Numerical simulation of dynamic response of underwater supercavitating projectile structure based on after-effect enhancement of kinetic penetration. (March 2020) - Li, X; Yan, P; Tan, B; Zhao, Y L; Liang, W G
Abstract: Aiming at the underwater supercavitating projectile, a damage mode of enhanced effect after kinetic penetration is proposed. The structure of energetic projectile with prefabricated breaking groove is designed, which can not only ensure the projectile strength in underwater motion, but also release the filling agent to the interior of the target through the projectile fracture when hitting the target. Based on ANSYS/LS-DYNA finite element analysis software, the equivalent model of supercavitating energetic projectile penetrating low-carbon steel shell of mine in three-phase domain is established. The dynamic response of the projectile in the stage of underwater motion and penetration is obtained by analyzing the force of the key parts of projectile and observing the deformation of the projectile structure. By changing the initial velocity and landing angle of the projectile, analyzing the law of velocity variation and penetration depth of the projectile, observing the deformation of the projectile structure and the phenomenon of the energetic agent disperation when penetrating the steel plate, the quantitative conclusion of the damage effect of the energetic projectile on the typical mine target under different working conditions is obtained. The research results have reference value for the structural design and power evaluation of underwater supercavitating energetic projectile.